MR CLEAN: TOR Affects Treatment Efficacy in Patients With Acute Ischemic Stroke. Issue 2 (11th March 2015) - Zarifyan, Alla
An analysis of the MR CLEAN trial demonstrated a significant interaction between time from stroke onset to reperfusion and treatment effect, with the decrease in absolute risk difference between treated and untreated patients of almost 7% per hour ( P  = .038). The relationship between time to treatment and treatment effect was not statistically significant but is still considered biologically plausible.